Attitudes to Income Inequality: Experimental and Survey Evidence - Andrew E. Clark; Conchita D'Ambrosio (Institute for the Study of Labor (IZA), 2014)
We review the survey and experimental findings in the literature on attitudes to income inequality. We interpret the latter as any disparity in incomes between individuals. We classify these findings into two broad types of individual attitudes towards the income distribution in a society: the normative and the comparative view. The first can be thought of as the individual's disinterested evaluation of income inequality; on the contrary, the second view reflects self-interest, as individual's inequality attitudes depend not only on how much income they receive but also on how much they receive compared to others. We conclude with a number of extensions, outstanding issues and suggestions for future research.
Keywords: C91; D31; D63; I31; 330; attitudes; distribution; experiments; income inequality; life satisfaction; reference groups